Contribution of obesity to racial and ethnic disparities in the risk of fetal myelomeningocele: a population-based studyAJOG MFM at a Glance - Hiba J. Mustafa, MD, FACOG; Catherine T. Burns, BA; Mohammad H. Heydari, BBS; Ali Javinani, MD; Aurelian Bidulescu, MD, MPH, PhD; Mounira Habli, MD; Asma Khalil, MD, MSc (Elsevier, 2024)
BACKGROUND: Prepregnancy obesity and racial-ethnic disparities has been shown to be associated with meningomyelocele. OBJECTIVE: This study aimed to investigate the association of maternal periconceptional factors, including race-ethnicity and prepregnancy body mass index, with the prevalence of isolated fetal myelomeningocele. METHODS: This was a population-based cross-sectional study using Centers for Disease Control and Prevention birth data from 2016 to 2021. Major structural anomalies or chromosomal abnormalities were excluded. Race-ethnicity was classified as non-Hispanic White (reference population), non-Hispanic Black, non-Hispanic Asian, Hispanic, and others. Maternal prepregnancy body mass index was classified as underweight (<18.5 kg/m2), normal (reference group; 18.5-24.9 kg/m2), overweight (25-29.9 kg/m2), and class I (30-34.9 kg/m2), class II (35-39.9 kg/m2), and class III obesity (≥40 kg/m2). A chi-square test of independence was performed to identify factors significantly associated with myelomeningocele. These factors were then stratified into 3 adjusted clusters/levels. The prevalence was calculated per 10,000 live births. The Cochran-Armitage test for trend was used to detect any significant increasing or decreasing trends. RESULTS: A total of 22,625,308 pregnancies with live birth, including 2866 pregnancies with isolated fetal myelomeningocele, were included in the analysis. The prevalence of isolated fetal myelomeningocele per 10,000 live births varied among different racial/ethnic groups, with the highest prevalence found among the non-Hispanic White (1.60 [1.52-1.67]) and lowest among the non-Hispanic Asian (0.50 [0.40-0.64]) population. The prevalence significantly increased with body mass index, with the highest prevalence found in the population with class III obesity (1.88 per 10,000 live births). Subgroup analysis of the associations between the significant variables (obesity, diabetes, hypertension, and education) and each ethnicity in cases with myelomeningocele showed significant variations in prevalence of these variables among different racial/ethnic groups. Following the model with the 3 levels of adjustment described in the Methods section, prepregnancy overweight and class I, II, and III obesity remained significantly associated with the odds of isolated fetal myelomeningocele. The adjusted odds ratios were 1.32 (95% confidence interval, 1.19-1.46; P<.001) for overweight, 1.55 (95% confidence interval, 1.38-1.75; P<.001) for class I obesity, 1.68 (95% confidence interval, 1.45-1.94; P<.001) for class II obesity, and 1.73 (95% confidence interval, 1.47-2.04; P<.001) for class III obesity. Similarly, following the 3-level adjustment model, the obesity-mediated effect of maternal race-ethnicity on the odds of myelomeningocele remained significant (non-Hispanic Black: adjusted odds ratio, 1.03; 95% confidence interval, 1.02-1.05; P<.001; non-Hispanic Asian: adjusted odds ratio, 1.02; 95% confidence interval, 1.01-1.03; P<.001; Hispanic: adjusted odds ratio, 1.5; 95% confidence interval, 1.03-1.6; P<.001). The test for trend among different racial/ethnic groups did not show significant results across the past 6 years. However, the test for trend showed a significant increase in the prevalence of isolated myelomeningocele associated with class II and III obesity over the past 6 years. CONCLUSION: There has been a rising trend of fetal isolated myelomeningocele in pregnancies with maternal class II and III obesity over the past 6 years after adjusting for other covariates. Prepregnancy obesity, a modifiable risk factor, is a significant driver of racial/ethnic disparities in the overall risk for isolated fetal myelomeningocele.